EFEKTIVITAS METODE DRILL DENGAN TEKNIK MASTER PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Riza Faishol; Fathi Hidayah (INCARE, International Journal of Educational Resources, 2021)
This study aims to find out the effectiveness of the application of drill methods with MASTER techniques in the study of Islamic Religious Education at SMP Negeri 1 Genteng in the 2016/2017 school year. Based on the observations found that the learning conditions are not conducive because of the application of improper methods. This research is quantitative research. The type of research used in this study is experimental research. The research was conducted in two cycles with two meetings by applying drill methods using MASTER techniques. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. Data collection techniques used are observation, interview, test, and documentation. The data analysis used is independent T-test. Based on the discussion about the effectiveness of drill methods with MASTER techniques in PAI learning, it was concluded that the application of drill methods with MASTER techniques can make students motivated, happy, active, and able to improve the effectiveness of learners' learning during the learning process. From the calculation using the t-test test, it is known that ttes = 3,287 ≥ t5% = 0.16435 means that the nil hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, thus it can be concluded that the effectiveness of drill learning methods with MASTER techniques has effective results on PAI subjects.